2009
DOI: 10.1186/1757-5036-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional nanosecond electric field mapping based on cell electropermeabilization

Abstract: Nanosecond, megavolt-per-meter electric pulses cause permeabilization of cells to small molecules, programmed cell death (apoptosis) in tumor cells, and are under evaluation as a treatment for skin cancer. We use nanoelectroporation and fluorescence imaging to construct two-dimensional maps of the electric field associated with delivery of 15 ns, 10 kV pulses to monolayers of the human prostate cancer cell line PC3 from three different electrode configurations: single-needle, five-needle, and flat-cut coaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Second, we considered that the electric field itself may be saturating in the solution. However, a number of studies, using similar electric pulse exposure systems, have shown a proportional increase in uptake of markers of membrane permeabilization, such as propidium ion and Yo-Pro-1, on applied voltage at amplitudes far beyond those used in this study (24,28,29). The electric-field dependence was also corroborated by whole-cell patchclamp experiments in which the membrane resistance was reduced proportional to the applied energy to the system (30,31).…”
Section: Comparison Of Experimental and Model Resultssupporting
confidence: 72%
“…Second, we considered that the electric field itself may be saturating in the solution. However, a number of studies, using similar electric pulse exposure systems, have shown a proportional increase in uptake of markers of membrane permeabilization, such as propidium ion and Yo-Pro-1, on applied voltage at amplitudes far beyond those used in this study (24,28,29). The electric-field dependence was also corroborated by whole-cell patchclamp experiments in which the membrane resistance was reduced proportional to the applied energy to the system (30,31).…”
Section: Comparison Of Experimental and Model Resultssupporting
confidence: 72%
“…Therefore, a classical one, like the yo-pro-1 iodide 19,54 , was used to compare the PM permeabilization thresholds between the two markers (Supplementary Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…for the conductivity and permittivity of grey matter [ 30 ] was interpolated in Mathematica in order to estimate the values at 250 kHz (Table 2 ). The electro-quasistatic assumption is validated based on the fact that the frequency of the field corresponds to a wavelength (3.5 m) and skin depth (0.5 m) that are greater than the longest dimension in the geometry [ 31 ]. The brain subdomain was modeled as a 0.75 cm × 0.75 cm × 0.425 cm ellipsoid having a total volume of 1 cm 3 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%